Analysis of the Fuses’ Electro-Thermal Field - Pleşca, A. (Elektronika ir Elektrotechnika, 2010)
A theoretical study of electro-thermal field, which comes out at fuses type HBC (High Breaking Capacity), but not only, is shown in this paper. This study is achieved considering the electric fuse like an inhomogeneous body as a whole, the experimental data confirming the theoretical assumptions made initially. Also, on the basis of theoretical study, it stands out the influence of filled material upon fuses behaviour.